VALIDITY AND RELIABILITY INSTRUMENT OF MATHEMATICS TEACHERS’ PERCEPTION ON 21ST CENTURY LEARNING (Practitioner Research, 2023)
21st century learning (PAK21) is among the most well-known educational phenomena in Malaysia nowadays in the face of IR4.0. In order to enter the era of the 21st century learning, mathematics teachers required to discover advance methods, strategies and teaching techniques so that generation Z is able to navigate IR 4.0 while able to sustain national identity and possess high spiritual values. This study conducted a survey of 30 primary school mathematics teachers on 21st Century Learning in Jitra, Kedah. This study examines the validity and reliability of the instrument from the perspective of mathematics teachers on 21st century learning. The results found that the validity test, which is Bartlett’s test of sphericity and Kaiser-Mayer-Olkin (KMO) of sampling adequacy, is significant. Next, the reliability test shows a significant value when Cronbach’s Alpha value is 0.941.